2013
DOI: 10.1177/1076029613489597
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance in Patients Undergoing Hemodialysis and Effect of Hemodialysis on Aspirin Resistance

Abstract: The aim of this study was to evaluate the prevalence of aspirin resistance (AR) in patients undergoing hemodialysis (HD) and to assess the effect of HD on the results of the Multiplate test. A total of 54 patients undergoing HD were included in this study. Blood samples were taken just before and after the HD session. To determine AR, we used Multiplate test. Platelet aggregation values of the study population were 363.01 ± 225.69 aggregation unit (AU) × minutes before and 375.33 ± 254.05 AU × minutes after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Most studies report a HTPR rate of approximately 20% using MEA . In patients undergoing haemodialysis, 50% of patients had HTPR . Interestingly, in patients undergoing coronary artery bypass‐graft surgery, the HTPR rate increased postoperatively .…”
Section: Discussionmentioning
confidence: 46%
“…Most studies report a HTPR rate of approximately 20% using MEA . In patients undergoing haemodialysis, 50% of patients had HTPR . Interestingly, in patients undergoing coronary artery bypass‐graft surgery, the HTPR rate increased postoperatively .…”
Section: Discussionmentioning
confidence: 46%
“…In many studies, the relationship between chronic renal failure and AR has been established. 26,27 We also found that the creatinine level was one of the independent predictors of AR (OR: 37.565; 95% CI: 2.21-636.35; P = .012). In vivo and in vitro studies have shown the effect of hyperlipidemia on AR.…”
Section: Discussionmentioning
confidence: 52%
“…This could be explained by aspirin resistance, which is known to occur to a higher degree in patients on HD than in other patient populations. 56 Our patient sample was too small to adequately evaluate the response to ASA in patients on HD. To our knowledge, a link between carbamylation and ASA resistance has not been investigated before.…”
Section: Discussionmentioning
confidence: 97%